Community Services for Development of Specialized Print Media by Integrated Learning in Journalism Project Case study of Don Kai Dee Benjarong Village, Krathum Baen, Samut Sakhon. - อาษา, ประกิจ; ธรรมสังวาลย์, สุธาวัลย์ (Siam Communication Review, 2019)
The first objective of the Development of Specialized Print Media ‘Don Kai Dee wisdom’ was to study the history and the process in making Benjarong that could be used create image of Don Kai Dee Benjarong village. The second objective was to study the process in developing the Specialized Print Media that lead to receivers’ fulfillment of the idealistic self while experiencing Benjarong as Thai products identity. The last objective was to evaluate the result of community services for development of specialized print media ‘Don Kai Dee Wisdom’ of communication arts faculty, Siam University. The sample selected in this study comprised craftsman, manufacturer and tourist visitors who had visited Don Kai Dee wisdom exibition number 400. The result of development of specialized print media ‘Don Kai Dee wisdom revealed that provide and publish information, cooperating the Identity and creating the good Image of Don Kai Dee Benjarong village and insert the fulfill of idealistic self of the consumers while experiencing Benjarong which was developed to be 4 types of specialized print media (1) The books ‘Don Kai Dee Benjarong Village : Benjarong Wisdom’ (2) The infographic and video media showing the process of producing benjarong (3) The stationary set of Don Kai Dee Benjarong village and (4) Souvenirs set of Don Kai Dee Benjarong Village. The evaluation results of the specialized print media ‘Don Kai Dee Wisdom’ found that (1) The book development for provide information about Don Kai Dee Benjarong village was at good level. (2) The info-graphic development for publish information about Don Kai Dee Benjarong village was at very good level (3) The specialized print media development for cooperating the identity of Don Kai Dee Benjarong village was at good level and (4) The souvenir development for creating the good image of Don Kai Dee Benjarong village was at good level.